If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6x + -7 = 8 + 23 Reorder the terms: -7 + 6x = 8 + 23 Combine like terms: 8 + 23 = 31 -7 + 6x = 31 Solving -7 + 6x = 31 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '7' to each side of the equation. -7 + 7 + 6x = 31 + 7 Combine like terms: -7 + 7 = 0 0 + 6x = 31 + 7 6x = 31 + 7 Combine like terms: 31 + 7 = 38 6x = 38 Divide each side by '6'. x = 6.333333333 Simplifying x = 6.333333333
| 4x-8=3x-4 | | X/g-1=17 | | 6x^2-x-960= | | 9x^2=9x-32 | | 6-10x=88-24x | | 10.00+9x=127 | | 10.00+9x=100 | | 5x^2+3x= | | 3(2y-3)-4y=-3 | | -5+6x=3 | | 18=z/3+8 | | 5x+11=93-8x | | 9x-7x=0 | | 9(3y-5)-(8y+4)= | | 7.00+10.00x=87 | | -11-1=10 | | 6(x-2)=9x-3(2-1) | | -13.00+2.00x=15 | | 14.00-3.00x=2.00 | | 10.00+3.00x=55 | | 10.00+3.00x=46 | | 2p^2-p-12=-6 | | 4r^2-r=33 | | 4x=215 | | 3x^2+16x-387=0 | | 5n^2=45 | | 38*3+5= | | 21x-2+38x+5=180 | | 12m^2+2m-8=0 | | y=mx-6b | | 7/2k-1/14k=-3 | | 7h+8=10h-7 |